2012
DOI: 10.1007/s00394-011-0294-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasma homocysteine level and hepatic sulfur amino acid metabolism in mice fed a high-fat diet

Abstract: This study suggests that plasma homocysteine level is increased in obesity-associated hepatic steatosis, possibly as a result of increased hepatic homocysteine efflux along with an altered sulfur amino acid metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…Our data showed that HFD significantly increased plasma homocysteine concentration. This is in agreement with previous studies showing that HFD increases plasma homocysteine concentration (Yun et al, 2013). Interestingly, SAM improves vascular dysfunction without decreasing homocysteine concentration.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data showed that HFD significantly increased plasma homocysteine concentration. This is in agreement with previous studies showing that HFD increases plasma homocysteine concentration (Yun et al, 2013). Interestingly, SAM improves vascular dysfunction without decreasing homocysteine concentration.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, SAM treated rats did not exhibit differences in serum total cholesterol, LDL cholesterol, HDL cholesterol, and FFA compared to HFD-fed rats (Table 1). As expected and in accordance with previous studies (Yun et al, 2013), administration of HFD significantly increased plasma homocysteine concentration (Fig. 1C).…”
Section: Sam Improves Endothelial Function In Hfd-fed Ratssupporting
confidence: 93%
“…Previous studies have suggested that increased circulating homocysteine level is probably due to reduced CBS activity [11][12][13]. Activation of CBS activity by salvianolic acid A markedly reduced the plasma level of homocysteine in rats fed with HFD [12].…”
Section: Discussionmentioning
confidence: 99%
“…The elevation of homocysteine level in NAFLD/NASH may result from inhibition of CBS activity [11][12][13] or protein expression [15]. However, the underlying molecular mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies showed that changes in plasma homocysteine level in obese or diabetic conditions were dependent on the type of experimental animal model used [6][7][8]. Plasma total homocysteine concentration increased by 1.6-fold in obese mice fed a high-fat diet for 12 weeks [7], but was 40% lower in db/ db mice, obese type 2 diabetic animals with a G-to-T point mutation of the leptin receptor [6]. In contrast, plasma homocysteine levels were similar between control rats and non-obese type diabetic Goto-Kakizaki rats [8].…”
Section: Introductionmentioning
confidence: 99%